MONITORING CLIMATE EXTREME EVENTS TREND IN NIGERIA USING CLIMPACT2 SOFTWARE - Yahaya, Otori Muhammed; Ogolo, E. O.; Agele, S. O.; Olanrewaju, A. V. (FUDMA Journal of Sciences, 2024)
Monitoring Nigeria climate extremes is essential for building resilience, reducing vulnerabilities, and ensuring sustainable development in the face of Nigerian changing climate. ClimPACT2 software is used in this research to quantify climate extreme indices rate of change in the three Nigerian climate zones. The weather inputs were daily precipitation, minimum and maximum air temperatures secondary data obtained from ERA5 from 1979 to 2021. The peaks of the maximum day and night temperatures were observed to be on significant increase in all the regions. WSDI is significantly increasing per year in the Savannah by about 1.19 and 1.14, 1.10 in monsoon and 0.50 in Sahel regions. CDD is significantly increasing per year by about 0.33 in Akure, 0.44 in Lokoja, 0.12 in Port Harcourt and insignificantly by about 0.46 in Katsina while CWD is observed to be decreasing in all the regions. The number of wet and very wet days were observed to be decreasing over the years indicating drying days. SPEI drought index on time scales of 3, 6, 12 and 24 revealed significant increase in short time scale drought magnitudes of about 0.001 in Sahel while no significant change was observed in monsoon region. The analysis has shown significant warming trends in the Nigerian climate zones with significant implication on our climate, agriculture and overall environment leading to ecosystem disruptions. It is crucial for policymakers and stakeholders to take note of these trends and consider implementing measures to mitigate its impacts